Injection Molding of Stainless Steel (SUS 316L) Powder Using a Thermoplastic Binder System - Ibrahim, Rosdi (2002)
The thesis presents the results of the investigation carried out to determine the effect of injection pressure and temperature, sintering temperature, sintering atmosphere, volume fraction of powderlbinder mixture and composition of the binder system on the properties of 316L stainless steel specimens produced by the Metal Injection Molding (MIM) technique. The stainless steel powder of 16µm average particle size was mixed with a thermoplastic binder comprising polyethylene, paraffin wax and stearic acid in the ratios of 35/60/5, 30/60/10 and 25/60/15 respectively using a z-blade mixer at the temperature of 160°C. The volume fractions of the powder used in the investigation were 65% and 58%. The specimen of tensile test shape was molded using an 80-ton Arburg injection molding machine at various injection pressures and temperatures.